Computer-mediated collaborative writing in L2 contexts: an analysis of empirical research. Issue 8 (2nd November 2018) - Li, Mimi
ABSTRACT: Computer-mediated collaborative writing has been increasingly implemented in L2 contexts due to wider awareness of affordances and benefits of Web 2.0 technologies. A systematic review of empirical studies over the recent decade is called forth in order to arouse broadened knowledge and provide new insights in this promising area. This study reviews 21 representative articles on computer-mediated collaborative writing published from 2008 to 2017 in top-tier peer-refereed journals. Holistic analysis of these articles has been conducted, including context and technology, theoretical/pedagogical framework, writing task, research focus, and data and instruments. Three main themes are synthesized: (a) interaction/writing process, (b) writing products/outcome, and (c) students' perceptions, and specific research strands in relation to each theme are further discussed, supplemented with illustrative tables. Drawing on the analyses of these empirical studies, the researcher discusses pedagogical recommendations in terms of writing tasks, grouping, student training, and assessment, and addresses future research directions involving broader learning contexts, varied collaborative writing tasks, methodological innovation, and multiple research strands that deserve further examination.